A Multi-Market Model of Generic Promotion: Measuring Returns to U.S. Dairy Advertising - 김성훈 (한국농촌경제연구원, 2007)
This paper develops a multi-market model to analyse the indirect effects of generic advertising as well as the direct effects of generic advertising that were usually discussed in previous research. As results of analytical and numerical analyses, the paper provides theoretical and empirical evidence that the horizontal demand and supply linkages have an important role in the effectiveness of generic advertising on market. The results of simulation present that evaluation of the impact of generic advertising should consider the horizontal linkages. This paper, basically, agrees the positive returns to generic promotion. However, the paper also showcases the possibility of over- (or under-) estimation of the effectiveness of generic advertising.
Keywords: multi-market model; generic advertising; dairy market; multi-market model; generic advertising; dairy market